2005
DOI: 10.2475/ajs.305.4.259
|View full text |Cite
|
Sign up to set email alerts
|

(U-Th)/(He-Pb) double dating of detrital zircons

Abstract: Geochronology and thermochronology on detrital material provides unique constraints on sedimentary provenance, depositional ages, and orogenic evolution of source terrains. In this paper we describe a method and case-studies of measurement of both U/Pb and (U-Th)/He ages on single crystals of zircon that improves the robustness of constraints in each of these areas by establishing both formation and cooling ages of single detrital grains. Typically these ages correspond to crystallization and exhumation or eru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 79 publications
(48 reference statements)
3
96
0
Order By: Relevance
“…By contrast, the U-Pb isotope system in zircon, having an effective closure temperature in excess of 900°C (Lee et al, 1997;Cherniak and Watson, 2001), essentially records the time of its crystallization in the igneous rock. The combination of these low-and hightemperature zircon chronologies has revealed that zircons with old (>400 Ma) FT or U-Th-He ages are extremely rare in continental sediments such as those from the Mississippi, Gange and Indus Rivers (Carter and Moss, 1999;Carter and Bristow, 2000;Rahl et al, 2003;Campbell et al, 2005;Reiners et al, 2005). This finding is consistent with the view that first-cycle zircons derived from old igneous basements are minor.…”
Section: Provenance Of Detrital Zirconssupporting
confidence: 82%
“…By contrast, the U-Pb isotope system in zircon, having an effective closure temperature in excess of 900°C (Lee et al, 1997;Cherniak and Watson, 2001), essentially records the time of its crystallization in the igneous rock. The combination of these low-and hightemperature zircon chronologies has revealed that zircons with old (>400 Ma) FT or U-Th-He ages are extremely rare in continental sediments such as those from the Mississippi, Gange and Indus Rivers (Carter and Moss, 1999;Carter and Bristow, 2000;Rahl et al, 2003;Campbell et al, 2005;Reiners et al, 2005). This finding is consistent with the view that first-cycle zircons derived from old igneous basements are minor.…”
Section: Provenance Of Detrital Zirconssupporting
confidence: 82%
“…For example, crystallization or cooling ages of detrital minerals in a basin can be used to determine provenance (e.g., Adams and Kelley, 1998;Baldwin et al, 1986;Barbieri et al, 2003;Carrapa et al, 2006;Clift et al, 2006;Glotzbach et al, 2011;Gray and Zeitler, 1997;Hurford and Carter, 1991;Hurford et al, 1984;Kalsbeek et al, 2000;Kelley and Bluck, 1992;Kosler et al, 2002;Reiners et al, 2005;Spiegel et al, 2007;Vermeesch et al, 2009;von Eynatten et al, 1996;Watt and Thrane, 2001). By comparing depositional ages with the cooling ages for detrital minerals, the timescales for erosion and transport in orogenic settings can be ascertained (Brandon and Vance, 1992;Bullen et al, 2001;Cerveny et al, 1988;Copeland and Harrison, 1990;Corrigan and Crowley, 1992;Garver and Brandon, 1994;van der Beek et al, 2006van der Beek et al, , 2010.…”
Section: Detrital Mineral Thermochronologymentioning
confidence: 99%
“…Although classic petrographic and geochemical approaches are still commonly used (Morton, 1985;Garzanti et al, 1996), isotopic techniques offer improved resolution of source-sink problems. Examples include: U-Pb ages in zircons (see review by Fedo et al, 2003), 40 Ar/ 39 Ar age dating of detrital micas (Cerveny et al, 1988;Renne et al, 1990;Hodges et al, 2005) and K-feldspars (Copeland et al, 1990), combined U-Th/HePb double dating (Reiners et al, 2005), and fission track analyses on detrital zircons (Brandon and Vance, 1992) and apatites (Donelick et al, 2005). However, once grainsize falls below that of sand (i.e., silt), the availability of robust provenance techniques becomes limited.…”
Section: Introductionmentioning
confidence: 98%